ASSESSMENT OF FACTORS INFLUENCING INDUSTRIAL SECTOR DEVELOPMENT BASED ON ECONOMETRIC MODELLING - Ne’matov Shokhrukhbek Mamurjon ogli (The latest news and research in education, 2025)
This article examines the influence of various economic determinants on industrial sector development using econometric modelling techniques. The study aims to identify key factors, measure the degree of their impact through quantitative indicators, and provide analytical results that may be applied in strategic planning and policy optimization. The findings can serve as a scientific basis for improving industrial competitiveness, strengthening forecasting potential, and developing more effective management decisions for long–term industrial sustainability.